PENGUJIAN TOKSISITAS AKUT LOGAM TIMBAL (Pb), KROM (Cr) DAN KOBALT (Co) TERHADAP Daphnia magna - AI Silmi (JURNAL TECHLINK, 2018)
This study aimed to analyze the LC50 value of metallic lead (Pb), chromium (Cr), and cobalt (Co)contained in the printing industry wastewater to Daphnia magna and analyze the relationship of these metals to the LC50 value. The measurement results konsnetrasi Pb and Cr do not exceed the quality standards established, but the metals Co exceeds quality standards. Toxicity of Pb, Cr, and Co were tested in static test using artificial solution of Pb, Cr, and Co in accordance with the concentration measured in the wastewater. Tests carried out consisted of two stages: a preliminary test and test base. Daphnia magna mortality data were analyzed using Probit method with the EPA program Probit Analysis Program Version 1.5. 24-hour LC50 value of Pb, Cr, and Co to Daphnia magna is 1.052% and the LC50 values of Pb, Cr, and Co are respectively 0.003 mg / l, 0.008 mg / l and 0.009 mg / l. All three metals have included the category of very toxic to Dahnia magna.